Novel catalytic hydrosilane mediated reduction reactions - Stoll, Emma (2021)
This thesis starts with an introduction to the relevant organosilicon and reduction chemistry concepts that underpin the chemistry that is explored in later chapters. In particular, hyperconjugation, relevant organosilicon reagent classes and reduction of carbonyl containing compounds are explored.